Uncovering Pregnancy Maintenance Cognitions of Housewives With Stunted Children in Makassar City - Ibrahim, Irviani Anwar; Kamaruddin, Syamsu A.; Adam, Arlin; Bastiana, Bastiana; Syukur, Muhammad (Public Health of Indonesia, 2025)
Background: Stunting is a chronic nutritional problem characterized by a child’s height being shorter than the age-standard, primarily resulting from prolonged inadequate nutritional intake. According to the Indonesian Nutrition Status Survey (SSGI) in 2022, the prevalence of stunting in Indonesia was 21.6%, with Makassar City reporting a rate of 18.4%. However, data from the Indonesian Health Survey (IHS) in 2023 indicated an increase in Makassar’s prevalence to 25.4%. Objective: This study aims to explore the cognitive understanding of housewives in Makassar City regarding pregnancy maintenance and its relation to stunting prevention. Methods: A post-positivistic paradigm was applied using a descriptive qualitative design. Data were collected through in-depth interviews with participants to gain a comprehensive understanding of their perceptions and practices. Results: The findings reveal that most participants possess a basic understanding of pregnancy care and actively utilize available health services, including community health centers (puskesmas), integrated service posts (posyandu), and hospitals. Nevertheless, cultural beliefs and local traditions, such as food restrictions and ritual practices during pregnancy, continue to influence maternal behaviors. Furthermore, several participants demonstrated a limited understanding of stunting, often associating it solely with “malnutrition” or “short stature,” without fully recognizing its underlying causes or long-term developmental impacts. Conclusion: These findings underscore the need for culturally sensitive and sustainable educational interventions within maternal health services to enhance awareness and promote effective strategies for stunting prevention. Keywords: stunting; pregnancy; maternal health; local culture